One Bloodline, Multiple Religiosities: Malay-speaking Hadramis on Being ‘Moderate-most’ Muslims in Contemporary Indonesia - Taufik, Egi Tanadi; Kurniawan, Syamsul; Suprianto, Bibi; Fitriyani, Feny Nida; Miftah, Muhammad (JSW (Jurnal Sosiologi Walisongo), 2024)
Internal contestation within Muslim communities over who embodies the ideal of moderation is often problematic, including among the descendants of the 18th-century Hadrami Arab diaspora in the Archipelago. Through qualitative research focusing on the Hadrami community dynamics in Pontianak, this article reveals divisions and internal conflicts within the community, leading to a contest over who could claim to be the most moderate. The study situates the exceptionalism of Hadrami elites in Pontianak within a "religious field," following Bourdieu’s framework, and draws on Rijal’s (2024) concept of viewing “Ḥabā’ib as symbolic capital” in religious competence, which is reinforced by their exclusive lineage, symbols, and rituals. This pursuit of Hadrami exceptionalism in moderation, in turn, gave rise to a sense of moral obligation referred to as "the Hadrami man’s burden." While theological and philosophical debates surrounding religious moderation persist, various perspectives at the vernacular level converge on the idea that being a moderate Muslim represents the virtuous ideal, forming the core of the ideological system through which some elites assert and cultivate their influence and power.__________The original draft of this article has been presented at the 23rd Annual International Conference on Islamic Studies (AICIS), February 1-4, 2024, at Universitas Islam Negeri Walisongo Semarang, Indonesia.